THE MULTIFACTOR MATHEMATICAL MODEL FOR CONSTRUCTING A MULTITUDE OF CONSISTENT EDUCATIONAL PATHS FOR TRAINING FULL STACK SPECIALISTS - Kozlov, Vyacheslav; Guryanov, Alexander; Alonceva, Elena (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2020)
The modern labor market, especially in the field of information technology startups, requires the training of a sufficiently large number of specialists with competencies in creating the minimum viable product (MVP). The educational organization should be able to quickly form the trajectory of specialist training based on the challenges of the labor market, taking into account the dynamics of its change, while maintaining the integrity and consistency of the educational program. The mathematical model of the formation of an educational program is proposed taking into account a large number of variable parameters, which allows one to construct many possible training paths for specialists and select the optimal ones according to the criteria of cost, efficiency or laboriousness.